Saline solution in peripheral venous: a literature review. - Lolita Dopico; Francimar Tinoco de Oliveira (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
One is about a research of bibliographical revision that objectified to analyze the scientific article summaries on the event of the practical one of the salinization in peripheral venous catheters in adult patients indexed in the data base National Library of Medicine (MedLine) in the period of 1995 the 2005, LILACS and the electronic database secondary OVID in this was used exactly time. The sample was constituted of five summaries and analyzed how much to the country and periodic of publication where the study it occurred, its delineation, conclusive size of the sample, and results or not how much to the effect of the salinization in the maintenance of the vascular patência. The results show two studies that confirm the salinization as efficient method in the maintenance of the permeability of the catheter, others two deny the effectiveness and one is inconclusive. One concluded that the thematic one presents modest production that does not contribute to congregate evidences concerning the effectiveness of the salinization in peripheral catheters in adults demanding new research for validation of the method. Key words: Nurse, saline solution, peripheral catheter